The princess of Trelian - Knudsen, Michelle (Candlewick Press, 2017)
Princess Meglynne of Trelian will soon be named the princess-heir, next in line to be queen, but her link to the dragon Jakl makes the kingdom's people more than a little uneasy, while a mysterious magical attack and some ominous divinations reveal that a much more powerful enemy may soon reappear and endanger them all.